Maximization of furanic compounds formation by dehydration and hydrogenation of xylose in one step over SO3-H functionalized H-beta catalyst in alcohol media - Gupta, Anshita; Nandanwar, Sachin U.; Niphadkar, Prashant; Simakova, Irina; Bokade, Vijay (Biomass & Bioenergy, 2020)
Furanic compounds such as furfural (FUR); furfuryl alcohol (F. Alc) are important renewable platform chemicals can be used as such or further convert for preparation of other value added products such as Levulinic acid (LA), Alkyl Levulinates, 2-Methyltetrahydrofuran (MTHF), and Tetrahydrofuran (THF) etc. Sulfonated H-beta zeolite was successfully prepared and used for the synthesis of furanic compounds especially FUR and F. Alc from c-xylose in one step using isopropanol as alcohol media. Prepared catalyst was well characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), BET, NH3-Temperature programmed desorption (TPD) and carbon-hydrogen-nitrogen-sulfur analysis (CHNS). It was found the total acid amount was increased with increase in sulfur loading which confirmed the sulfonic acid group (SO3-H) was successfully grafted onto zeolite structure. 3 wt% H-beta-SO3-H catalyst with optimized reaction parameters of 150 degrees C, 7 h, 25 wt% catalyst loading was tuned to get the highest furanic compound yield of 88.5% (FUR 76.8% + F.Alc 11.7%).The reusability study confirmed that there was a marginal drop of similar to 25% after 3 recycle runs.
Keywords: furfural; Furfuryl alcohol; H-beta; isopropanol; sulfonated zeolite; Xylose